Proteogenomics of Pristionchus pacificus reveals distinct proteome structure of nematode models - Borchert, Nadine; Dieterich, Christoph; Krug, Karsten; Schütz, Wolfgang; Jung, Stephan; Nordheim, Alfred; Sommer, Ralf J.; Macek, Boris (Genome Research, 2010)
Pristionchus pacificus is a nematode model organism whose genome has recently been sequenced. To refine the genome annotation we performed transcriptome and proteome analysis and gathered comprehensive experimental information on gene expression. Transcriptome analysis on a 454 Life Sciences (Roche) FLX platform generated >700,000 expressed sequence tags (ESTs) from two normalized EST libraries, whereas proteome analysis on an LTQ-Orbitrap mass spectrometer detected >27,000 nonredundant peptide sequences from more than 4000 proteins at sub-parts-per-million (ppm) mass accuracy and a false discovery rate of <1%. Retraining of the SNAP gene prediction algorithm using the gene expression data led to a decrease in the number of previously predicted protein-coding genes from 29,000 to 24,000 and refinement of numerous gene models. The P. pacificus proteome contains a high proportion of small proteins with no known homologs in other species (“pioneer” proteins). Some of these proteins appear to be products of highly homologous genes, pointing to their common origin. We show that >50% of all pioneer genes are transcribed under standard culture conditions and that pioneer proteins significantly contribute to a unimodal distribution of predicted protein sizes in P. pacificus, which has an unusually low median size of 240 amino acids (26.8 kDa). In contrast, the predicted proteome of Caenorhabditis elegans follows a distinct bimodal protein size distribution, with significant functional differences between small and large protein populations. Combined, these results provide the first catalog of the expressed genome of P. pacificus, refinement of its genome annotation, and the first comparison of related nematode models at the proteome level.